Additive manufacturing and direct synthesis of sphene ceramic scaffolds from a silicone resin and reactive fillers. Issue 1 (January 2022) - Elsayed, Hamada; Sayed, Mona; Naga, Salma M.; Rebesan, Pietro; Gardin, Chiara; Zavan, Barbara; Colombo, Paolo; Bernardo, Enrico
Highlights: The article reports on the direct synthesis and additive manufacturing of Sphene (CaTiSiO5 ) bioceramic scaffolds. The fabricated scaffolds with hierarchical porosity from 59 to 74%, exhibited a compressive strength from 3.9 to 12.7 MPa. Sphene scaffolds showed bioactivity with immersing in SBF solution and chemical stability with slow ion release. The sphene scaffolds exhibited adequate cell viability and no cytotoxicity effect. Abstract: Sphene (CaTiSiO5, i.e. CaO·TiO2 ·SiO2 ) ceramics were successfully developed via the polymer derived ceramics route, starting from a commercial silicone containing specific oxide fillers. The approach allowed the combination of synthesis, in conditions of high phase purity, and advanced manufacturing. In particular, the adopted starting materials enabled an easy preparation of pastes, to be used for direct ink writing (DIW) of three-dimensional reticulated scaffolds. Sphene scaffolds, after firing at 1300 °C, were always regular and crack-free, despite changes in the line spacing, resulting in variable porosity (from ≈ 59 to 74 %), and exhibited a compressive strength from 3.9 to 12.7 MPa. The porosity was actually hierarchical, considering the formation of 'spongy' struts. In vitro tests, with increasing immersion time in SBF solution, confirmed the bioactivity, combined with a quite slow ion release, useful to maintain the pH value at nearly physiological values. Additional biological tests, consisting of the seeding of scaffold with normal human adult dermal fibroblasts, showed adequate cell viability and no toxicity effect.